Homer1a Attenuates Endoplasmic Reticulum Stress-Induced Mitochondrial Stress After Ischemic Reperfusion Injury by Inhibiting the PERK Pathway - Wei, Jialiang; Wu, Xiuquan; Luo, Peng; Yue, Kangyi; Yu, Yang; Pu, Jingnan; Zhang, Lei; Dai, Shuhui; Han, Donghui; Fei, Zhou (Frontiers in Cellular Neuroscience, 2019)
Homer1a is the short form of a scaffold protein that plays a protective role in many forms of stress. However, the role of Homer1a in cerebral ischemia/reperfusion (I/R) injury and its potential mechanism is still unknown. In this study, we found that Homer1a was upregulated by OGD (oxygen and glucose deprivation) and that overexpression of Homer1a alleviated OGD-induced Lactate Dehydrogenase (LDH) release and cell death in cultured cortical neurons. After OGD treatment, the overexpression of Homer1a preserved mitochondrial function, as evidenced by less cytochrome c release, less ROS production, less ATP and MMP (mitochondrial membrane potential) loss, less caspase-9 activation, and inhibition of ER stress confirmed by the decreased expression of phosphate-PKR-like ER Kinase (p-PERK)/PERK and phosphate- inositol-requiring enzyme 1 (p-IRE1)/IRE1 and immunofluorescence staining. In addition, mitochondrial protection of Homer1a was blocked by the ER stress activator TM (Tunicamycin) with a re-escalated ROS level, increasing ATP and MMP loss. Furthermore, Homer1a overexpression-induced mitochondrial stress attenuation was significantly reversed by activating the PERK pathway with TM and p-IRE1 inhibitor 3,5-dibromosalicylaldehyde (DBSA), as evidenced by increased cytochrome c release, increased ATP loss and a higher ROS level. However, activating the IRE1 pathway with TM and p-PERK inhibitor GSK2656157 showed little change in cytochrome c release and exhibited a moderate upgrade of ATP loss and ROS production in neurons. In summary, these findings demonstrated that Homer1a protects against OGD-induced injury by preserving mitochondrial function through inhibiting the PERK pathway. Our finding may reveal a promising target of protecting neurons from cerebral I/R injury.